The role of customer knowledge management towards organizational performance / Ahmad Suffian Mohd Zahari … [et al.] - Mohd Zahari, Ahmad Suffian; Abdul Rahman, Baharom; Othman, Abdul Kadir; Raja Baniamin, Raja Mariam (Faculty of Information Management, 2014)
In this information age, Knowledge Management (KM) and Customer Knowledge Management (CKM) have become the main competitive strategies of the organization to improve the organizational performance. This paper discusses the role of Knowledge Management and Customer Knowledge Management implementation in improving organizational performance. Moreover, the paper also highlights the concept of Knowledge Management, Customer Knowledge Management and the related issues pertaining to this concept. This paper also traces the interactive processes between Knowledge, Knowledge Management practices and Customer Knowledge Management within the organization. Based on the discussion, it can be concluded that the implementation of Knowledge Management and Customer Knowledge Management in the organization can play a leading role in improving the organizational performance.